Promoting value addition among farmers in the cassava food value chain in Nigeria. Issue 9 (8th August 2018) - Donkor, Emmanuel; Onakuse, Stephen; Bogue, Joe; de los Rios Carmenado, Ignacio
Abstract : Purpose: The purpose of this paper is to analyse the effects of the determinants of farmer participation in value addition through cassava processing in Nigeria. Design/methodology/approach: This study employs the probit model to analyse the determinants of farmer participation in value addition whereas the Tobit model is used to investigate the determinants of the extent of producer's involvement in value addition using a data set of 400 cassava farmers drawn from the Oyo State of Nigeria. Findings: The findings further indicate that among other factors, human capital factors including farmer age and location variable tend to reduce farmer participation in value addition through processing whereas experience and record keeping promote farmer participation in cassava processing. Institutional variables, notably membership of farmer association, extension access and credit access, enhance farmer participation in value addition. Finally, ownership of a radio set, a television set and access to electricity strengthen the value-adding capacity of farmers. Research limitations/implications: This study only considers the determinants of producers' participation in cassava processing but does not explicitly analyse the impact of value addition on their profit margin. This issue would form a basis for future research to enhance knowledge in the extant literature. Practical implications: The study suggests that if the value-adding capacity of farmers is strengthened, rural economy is likely to be improved upon through the proliferation of rural food processing enterprises. Originality/value: Despite the relevance of developing food value chains in Africa and integrating farmers in them, there are limited studies on promoting value addition among farmers. This study contributes to narrowing this knowledge gap.